Attention to Place: Learning to Listen - MacDonald, Craig; Wiebe, Sean (Journal of the Canadian Association for Curriculum Studies, 2011)
In this paper we set out to explore the speculative function and nature of narrative in autoethnographic research. We consider how place–as locus, milieu, setting in which we narrate the distance between ourselves and events we can remember, places where we can remember being (or, in this case, becoming: becoming authors)–enriches our understanding of autoethnographic research in Education. Determining autoethnography as new frontier and as site for the construction of a way of life, we offer and invite beginnings in literary enjoyment of life through autobiographical writings for the Social Science of Education. We find ourselves digressing, and suggest that this may be a turn our memory takes on its homeward journey. We celebrate life.